Sexual dimorphism and length weight relationship in chestnut crab, Cardisoma carnifex Herbst, 1796 (Decapoda: Gecarcinidae) of Parangipettai stock, Tamilnadu, India - P. Kaarmugilan; M. Thangaraj (Arthropods)
The present study was conducted in the Parangipettai mangrove area of Tamilnadu, India, from November 2021 to April 2022, which aims to investigate the relationships between carapace length-weight and carapace width-weight of the chestnut crab, Cardisoma carnifex. A total of 129 crabs were examined, including 66 females and 63 males. Results indicated that males had a mean body weight of 343 ± 81.91 g, while females weighed 377.86 ± 86.28 g on average. Furthermore, females exhibited a significantly larger mean carapace length (6.32 ± 2.35 cm) compared to males (5.85 ± 2.10 cm). The correlation coefficient (r2) highlighted a stronger association between body weight (BW) and carapace width (CW) than BW and carapace length, indicating that variations in body weight were predominantly influenced by changes in carapace width. Positive relationships between carapace length and carapace width were observed in males (b = 1.0733, r2 = 0.9467), females (b = 1.0136, r2 = 0.9658), and both sexes combined (b = 1.0544, r2 = 0.9532). This sexual dimorphism, with females being larger than males, may suggest an adaptation associated with increased egg production. The study's findings provide valuable baseline data on the morphological characteristics of C. carnifex in the Parangipettai stock. Such information is essential for establishing ongoing monitoring and management strategies for this crab species, contributing to the conservation of biodiversity in the region.